Cost-effectiveness of preventing child internalising problems: Results from the translational trial of Cool Little Kids at school entry. (March 2020) - Chatterton, Mary Lou; Bayer, Jordana K.; Engel, Lidia; Rapee, Ronald M.; Beatson, Ruth; Hiscock, Harriet; Bretherton, Lesley; Wake, Melissa; Mihalopoulos, Cathrine
Highlights: Parent education prevented symptoms of anxiety and depression in shy children. Costs to the health care system were higher for children in the parenting group. Costs to society were not higher for children in the parenting group. Parent education is likely cost-effective for preventing anxiety and depression in children. Abstract: Objective: A translational trial evaluated the effectiveness of screening for inhibited childhood temperament, followed by a preventive parenting program - Cool Little Kids . This study determined the cost-effectiveness from societal and health sector perspectives using trial data. Method: Resources to deliver the screening and parenting sessions were determined from study records. Parents completed a questionnaire reporting resources used at one-year follow-up. Standard Australian unit costs were applied. Clinical outcomes for children and parental quality adjusted life-years (QALYs) were used to calculate incremental cost-effectiveness ratios (ICERs). Results: Total societal costs were lower, but non-significant for the intervention compared to the control group (mean difference -$500 p = 0.937). Total health sector costs were significantly greater (mean difference $1, 956; p = 0.015). The intervention led to significantly fewer internalising symptoms (Strengths and Difficulties Questionnaire (SDQ)-emotional difficulties adjusted mean difference −0.5; p = 0.006), fewer children with SDQ-emotional symptoms in the abnormal range (24.2 % vs. 33.0 % p = .014) and fewer with diagnosed anxiety (44.2 % vs. 50.2 % p = 0.427). From the societal perspective, the intervention would likely be cost-effective. Health sector ICERs were $1, 171/SDQ-emotional symptom decrease, $51/abnormal SDQ avoided and $77/anxiety case avoided. Conclusions: This economic analysis alongside an implementation study provides an early indication that Cool Little Kids may be cost-effective.